Current approaches and utilization of new screening techniques for evaluation of FHB resistance at CIMMYT. - Schlang, N.; Duveiller, E. (Plant Breeding and Seed Science, 2011)
Fusarium head blight (FHB) is a major disease of wheat in most wheat growing areas of the world. Resis- tance to FHB is a key trait for CIMMYT and many wheat breeding programs worldwide. New plant pheno- typing techniques such as quantification of fungal biomass using real-time PCR have become available re- cently. CIMMYT’s approach is to test new techniques for their feasibility and to apply them in routine disease screening programs if they prove to be valuable. Two sets of spring wheat genotypes assembled on the basis of low (group 1) and high (group 2) FHB index observed in previous years, were phenotyped and genotyped in CIMMYT’s FHB screening program. Phenotyping consisted of visual disease scoring (FHB index), mycotoxin analysis (DON) and quantification of fungal biomass. Apart from the FHB index, the two groups differed slightly in terms of DON accumulation although no differences were observed for average fungal biomass. This observation combined with the lack of correlation between disease symptoms and amount of fungal biomass suggested that some useful informa- tion may not be considered to discriminate resistant from susceptible genotypes when field selection is solely based on visual scoring results. DON/biomass-ratio was assessed for all genotypes and was found to be higher in the more resistant group 1 contrary to expectiations. An increase in DON production resulting from a stress or from resistance is discussed as a possible hypothesis. The determination of fungal biomass proved to be potentially valuable as a phenotyping tool. Genotyping results also showed that new genotypes harboring moderate levels of resistance and differing from traditional sources of scab resistance become available.